Socio-Pragmatic Markers of Politeness Strategies - Paronyan, Shushanik; Vardanyan, Mane (Bulletin of Yerevan University B: Philology, 2025)
The aim of this paper is to investigate the socio-pragmatic factors influencing the use of politeness strategies in Oprah Winfrey’s interviews and to elucidate their role in creating effective communication and rapport-building in the realm of media discourse. Politeness is interpreted in terms of the verbal decisions made by the speakers, the linguistic phrases that create respectful verbal behaviour and convey friendliness to the communicative situation. The data analysis which is conducted on the material of Oprah Winfrey’s interviews with Michelle Obama, Lady Gaga, and The Rock, unveil the sociocultural intricacies that mold her conversational demeanor. It is concluded that Oprah Winfrey’s adept utilization of direct and indirect interrogative speech acts in the process of inquiry serves as a cornerstone for fostering authentic communication and building rapport within the setting of the talk show. By strategically incorporating direct questions alongside indirect ones, she creates an inclusive atmosphere that encourages the interviewees to share their personal experiences comfortably.